Penyederhanaan Rumus Grafik Barber Johnson Studi Kasus Di BLUD RSU Anshari Saleh Banjarmasin Tahun 2013 - Armiati Armiati; Safril Safril; Aris Antoni; STIKES Husada Borneo; Universitas Esa Unggul Jakarta (Jurnal Kesehatan Indonesia, 2014)
In hospital patient care, one of the data used to evaluate the efficiency of services in hospital is a Barber Johnson Chart. It was combined four parameters : BOR, aLOS, TOI and BTO. Based on observation and determination research study of BOR aid line created with complex steps. Determining the BOR value will be Mde it’s aid line to determine O value BOR formula and substitute O value to LOS formula and TOI, to search A x 365 of aLOS and TOI formula, to substitute A x 365 value of aLOS formula to A x 365 of TOI formula, eliminate D at last. The purpose of this research is to simplify Barber Johnson Chart formula by enabling the mathematical principles. The type of this research is descriptive analytical that present the calculation results of Barber Johnson Chart to use the simplified formula, The unit of analysis in this research is a basic data calculation of four parameters of Barber Johnson Chart in BLUD RS. Dr. H. Moch. Ansari Saleh. Simplification of the process obtained the formula TOI = (100% - BOR)/B0R and aLOS = 1. The calculation result of four parameters Barbet Johnson Chart to use the simplified formula and according to Soejadi, it was 95 percent the same result as well as to display of Barber Johnson Chart Image showed the same .